2016
DOI: 10.1128/genomea.01294-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences for Three Chromosomes of the Burkholderia stabilis Type Strain (ATCC BAA-67)

Abstract: We report here the complete annotated genome sequence of the Burkholderia stabilis type strain ATCC BAA-67. There were three circular chromosomes with a combined size of 8,527,947 bp and G+C composition of 66.4%. These characteristics closely resemble the genomes of other sequenced members of the Burkholderia cepacia complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Molecular epidemiological investigations were carried out using core genome multilocus sequence typing (cgMLST) analysis with Ridom SeqSphere+ v3.2.1 (Ridom, Münster, Germany) [ 41 ]. Reads were quality trimmed to ≥ Q30 and mapped against the reference genome of B. stabilis type strain ATCC27515 BAA-67 (GenBank accession numbers CP016442–4) [ 42 ]. A minimum coverage of 10x was needed for mapping.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular epidemiological investigations were carried out using core genome multilocus sequence typing (cgMLST) analysis with Ridom SeqSphere+ v3.2.1 (Ridom, Münster, Germany) [ 41 ]. Reads were quality trimmed to ≥ Q30 and mapped against the reference genome of B. stabilis type strain ATCC27515 BAA-67 (GenBank accession numbers CP016442–4) [ 42 ]. A minimum coverage of 10x was needed for mapping.…”
Section: Methodsmentioning
confidence: 99%
“…This draft comprises 1 contig for each of the 3 chromosomes. Comparison with the genome of B. stabilis BAA-67 ( 16 ) showed that the genomes are syntenic with the exception of a rearrangement on chromosome 1 between the rRNA operons, which might be a real inversion or an assembly artifact in 1 of the genomes (Figure 1). We detected a separate contig representing a predicted plasmid sequence, whereas none was found within strain BAA-67 (J. Bugrysheva, US Centers for Disease Control and Prevention, pers.…”
Section: Resultsmentioning
confidence: 99%
“…We manually compared assemblies in Artemis and ACT ( 14 , 15 ) to circularize and split chromosomes 1 and 2 according to the genome of B. stabilis BAA-67 (GenBank accession nos. CP016442–4) ( 16 ). We found chromosome 3 is a single contig that was not obviously circularizable.…”
Section: Methodsmentioning
confidence: 99%